Estimating the Impacts of Capital Bikeshare on Metrorail Ridership in the Washington Metropolitan Area. Issue 7 (July 2019) - Ma, Ting; Knaap, Gerrit-Jan
Bikeshare programs have transformed the urban transportation landscape. However, their impacts on rail transit have not been fully examined. Some researchers find shared bikes help reduce the first-mile/last-mile gaps and boost rail transit ridership, although others see bikeshare as a competitor for riders. Previous studies have mostly relied on surveys of bikeshare program users as the data source, and few have addressed this question using more rigorous methods. In this paper, the authors take the Washington metropolitan area as an example and use statistical methods to quantify the impact of the bikeshare program on rail transit ridership. Using detailed ridership data between 2010 and 2015, they break down Metrorail ridership by type (entries vs. exits) and time of the day (AM peak vs. PM peak) to analyze how Capital Bikeshare (CaBi) interacts with Metrorail. Furthermore, Metrorail stations are categorized into core stations and peripheral stations to examine the impacts of CaBi in different built environments. Regression results show that the impacts of CaBi vary by Metrorail station location. For core Metrorail stations, CaBi docking stations within ¼-mile of a Metrorail station reduce rail ridership in all measures. In particular, CaBi would reduce the number of AM-peak exits by 4, 738 per station per month. However, CaBi complements Metrorail in peripheral neighborhoods. Having CaBi installed nearby would increase monthly Metrorail ridership by 1, 175 AM-peak exits, 1, 417 PM-peak entries, 2, 284 AM-peak entries, and 2, 422 PM-peak exits. Based on the findings, the authors suggest a collaboration between Metrorail and CaBi to add more bikeshare stations within ¼-mile of peripheral Metrorail stations to increase the ridership of both systems.